La Garantía para Parturientas en cuanto a la Inembargabilidad de la Remuneración, Limita el Interés Superior del Niño - Chimbo Ayala, Beberlyn Estefany (2021)
In a work environment where the main characters are pregnant women a stable and complete remuneration is essential, in order to guarantee physical, economic and social stability of pregnant womwn, but for this is necessary the exitence and correct application of rules that can guarantee said guarantees for the efective fulfillment of the rights of pregnant workers. The retention or garnishment of the remunertion established in article 92 of the Labor Code. Has generated the development of a Deep investigation of said guarantee, for wich aspects and opinions favorable to said group od women have been generated, in such a way tht it seek to deepen the subject to safeguard the life of the mother as well as the correct development of the child inside the womb and once it is born, that is, during its first years of life, fundamentl,years for the correct developent of the citizen The present investigation, examine economic, social and juridic problems, causing the garnishment of remunerations to the large group of pregnant workers within our nation, that`s why, by and for them, some research methods were developed, aimed at finding efficient alternative solutions to the latent problem. The main results werw generated base don in-depth research with practicing lawyers, as well as with professionl experts in the labor field, wich generated positive results for the change of the norm to extend the retention periodo r garnishment of the estalished in order to avoid health alterations in the life of the nother and the unborn child.